Analysis on Relation Between Economic innovation models and Bank roles - Dinh Tran Ngoc Huy; Pham Anh Dung; Le Ngoc Nuong; Le Thi Han; Do Thi Sang Ms; Dinh Tran Ngoc Hien; MSc Pham Hung Nhan (Generasi Sains Indonesia, 2024)
This paper interprets the connections between economic innovation models and banking roles in the past few years. The methodological methodology includes qualitative research, or synthesis and inductive. According to Savvides et al. (2003), domestic research and development as well as foreign direct investment help in rising domestic productivity and value-added growth, recent researches support the same results. The SWOT framework is extended with the help of one more value-analysis element. The findings show that green technology helps Vietnam to expand its market and consumer base, and green transformation will increase the export potential of firms and allow them to enter the global supply chain.